Evaluation of Passenger Service at Board of KMP. Trevallies on Bastiong - Sofifi Tracking, North Maluku Province - Doharman Lumban Tungkup; Surnata Surnata; Syadza Yasminra (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2019)
North Maluku province that thousands Kota Ternate is located at the foot of Mount Gamalama for 11 (eleven) years and after 11 (eleven) years of transition and preparation of infrastructure, capital of North Maluku province was transferred to the City of Sofifi located on Halmahera Island is an island greatest. Bastiong harbor crossing in the city of Ternate serves to connect the three (3) separate island with waters of Ternate, Tidore and Halmahera. For the creation of services that match the level of passenger service, the necessary analysis using the method of conformance level of minimum service standards with existing conditions. Based on this analysis it was concluded that there are variables that are still lacking in the service of some ferry transport as not Information not available yet and Safety Facility that is easily visible and affordable form of health workers, wheelchair and stretcher, Has not provided information security problems are easily visible and clearly legible, not yet available proper temperature control facilities, toilet facilities according to the needs of passengers, canteen / cafeteria clean and separate from the passenger space as well as using electric stoves, are not yet available facilities Wheelchairs and Special Room Special Room facilities Wheelchairs users.